Lettercard from Éamonn Duggan to his fiancée May Kavanagh, written after his release from prison - Duggan, Éamonn, 1874-1936; Duggan, May (1917)
Writing to Kavanagh from Longwood, Co. Meath on July 4 1917, Duggan refers to his feelings on coming home from prison - 'how completely unnerved + queer I felt during those days of excitement in Dublin'.
Duggan joined the Irish Volunteers on their foundation and fought at the North Dublin Union and later Fr. Mathew Hall during the Easter Rising. He was subsequently imprisoned in Mountjoy, Portland and Lewes prisons, was among those released in the summer of 1917 and successfully stood as a Sinn Féin candidate for South Meath in 1918.
Keywords: Duggan, Éamonn, -- 1874-1936; Sinn Féin; Ireland -- History -- Easter Rising, 1916 -- Prisoners and prisons